If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u + 307 = 927 Reorder the terms: 307 + u = 927 Solving 307 + u = 927 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-307' to each side of the equation. 307 + -307 + u = 927 + -307 Combine like terms: 307 + -307 = 0 0 + u = 927 + -307 u = 927 + -307 Combine like terms: 927 + -307 = 620 u = 620 Simplifying u = 620
| -14+8n=-2+2(4n-6) | | -2n-4=-24 | | (8+7)+(9-2)=18 | | 6r+9=6(r+1)+3 | | v/-28=-31 | | 4x-4=4+X+3 | | 12+x=15-12x | | 10r+5=35 | | c-13.7=-10.7 | | 2(x-5)+3x=4x-3 | | -16=m/3-20 | | y+82=591 | | 3r-28=8(1+4r)+7r | | 30z=450 | | 2=m/4-1 | | Log(4)8x+log(4)4=3 | | -31=c/-16 | | 6=-2(3p+3) | | 2y+13=2y+19 | | 350x+xy-200=0 | | c+-102=277 | | -4x-4=32 | | -p-4=2 | | -0.26=log(x) | | 11-3f=2 | | 3.8/4 | | -8x^2+3-10x=0 | | 5(-4x+7)=175 | | m+-77=-50 | | -p+2=-3 | | -3c=-81 | | -75=v-83 |